Development and characterization of low cost planar interdigital ammonia sensor for water quality sensing application - Jalal, Norfarah Amira (2017)
The existing of ammonia in the aquatic habitat was normally caused by the aquatic life itself. Previous study proves that exceeding ammonia in the water can cause the pH level to increase. In order to make sure the ammonia level was at the allowable range, the monitoring system including of ammonia sensor is needed. This thesis presents three types of planar interdigital sensors that have been fabricated and developed for the use of aquaculture monitoring process. The main objectives of this study is to develop an affordable, low — cost ammonia sensor for aquaculture industry by designing, developing, characterizing, and evaluating the proposed new sensor that is suitable for observing and detecting the contamination level caused by ammonia in water. There are several experiments conducted on these planar interdigital sensors to recognize which sensor produces a better sensitivity and performance. The sensor were tested and experimented with different type of material under test (MUT) including the different concentration of the Ammonium Chloride (NH4CI') ranging from O.lmg/L to 0.5mg/L. These planar interdigital sensors were designed with the same effective area but different number of positive electrodes and of negative electrodes. The optimum number of electrode is crucial during the designing process because it will affect on the diameter, d of the sensors. The experiment was carried out by using Impedance Analyzer IM3570 to gather an appropriate data in terms of performance and NI myRIO-1900 was used to test and evaluate the sensor for the application purposed. Since the output value from the sensor is relatively small, a signal conditioning system is developed as an interfacing system between the sensor and Data Acquisition (DAQ) system. Further development in Graphical User Interface (GUI) was carried out to analyze record and display all the results obtained during the experiment or testing period. Results shows that Sensor 1 has the best sensitivity compared to other sensors and it can be conclude that Sensor 1 has the better performance of sensitivity among the sensors with the percentage of 99.8% of the imaginary part sensitivity. This planar interdigital sensor can be used as a tool for aquaculture monitoring in the pisciculture farm where the ammonia level should not exceed 0.5mg/L.